Captain Underpants and the wrath of the wicked Wedgie Woman : the fifth epic novel - Pilkey, Dav, 1966- (New York : Scholastic, 2001)
"George and Harold have really done it this time--they've created a monster! She's faster, smarter, and more evil than anything the world has seen before--she's Wedgie Woman! With the help of her horrible robots and her horrendous hairdo, Wedgie Woman is on a mission to take over the world, and she'll give a whopping wedgie to anyone who stands in her way--including Captain Underpants."
Keywords: Escuelas -- Literatura juvenil